2023
DOI: 10.3390/ijms24043160
|View full text |Cite
|
Sign up to set email alerts
|

Frail Silk: Is the Hughes-Stovin Syndrome a Behçet Syndrome Subtype with Aneurysm-Involved Gene Variants?

Abstract: Hughes-Stovin syndrome is a rare disease characterized by thrombophlebitis and multiple pulmonary and/or bronchial aneurysms. The etiology and pathogenesis of HSS are incompletely known. The current consensus is that vasculitis underlies the pathogenic process, and pulmonary thrombosis follows arterial wall inflammation. As such, Hughes-Stovin syndrome may belong to the vascular cluster with lung involvement of Behçet syndrome, although oral aphtae, arthritis, and uveitis are rarely found. Behçet syndrome is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…There may be other reasons why HSS patients have more PAA, but fewer We have showed that isolated PAT and PAA have similar clinical findings and respond to the same immunosuppressive therapy, suggesting that they represent the same clinical spectrum (7,9). Importantly, cases with PAA who were previously documented to have solo PAT suggest that PAT could be indeed the precursor in this spectrum (7,29,49,75). On the HSS side, however, the concept of isolated PAT apparently has not been recognized yet.…”
Section: Histopathological Examination In Bothmentioning
confidence: 83%
“…There may be other reasons why HSS patients have more PAA, but fewer We have showed that isolated PAT and PAA have similar clinical findings and respond to the same immunosuppressive therapy, suggesting that they represent the same clinical spectrum (7,9). Importantly, cases with PAA who were previously documented to have solo PAT suggest that PAT could be indeed the precursor in this spectrum (7,29,49,75). On the HSS side, however, the concept of isolated PAT apparently has not been recognized yet.…”
Section: Histopathological Examination In Bothmentioning
confidence: 83%
“…After ruling out infectious etiology, septic emboli, and underlying coagulopathic disease, and based on the findings of multiple arterial aneurysms with venous thrombosis of large, medium, and small vessel thrombosis, a diagnosis in the presence of an aphthous ulcer was suspected to be Behcet's disease, which was later confirmed with a pathergy test. Incomplete Behcet's disease/Hughes-Stovin syndrome (HSS) was considered less likely due to the presence of aphthous ulcers, which are very rare in HSS [ 8 , 9 ]. Anticoagulation therapy was not initiated due to the high risk of bleeding.…”
Section: Case Presentationmentioning
confidence: 99%
“…17,18 Triggianese et al presented an interesting approach linking HSS to HLAB51 in their case report, which is in contradiction with Manole et al's work suggesting that HSS is a mainly vascular disorder associated with certain minor genetic variations that can interfere with proper vascular function. 4,5 These assumptions need further investigation but are hindered by the scarcity of patients. From the anatomical perspective, aneurysms may be single, multiple, unilateral or bilateral.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interesting hypotheses suggested that Hughes-Stovin syndrome may be attributed to an autoimmune disorder, whereas others propose a genetic predisposition or a potential combination of both factors. 4,5 The management of Hughes-Stovin syndrome is controversial due to its rarity and limited understanding. The primary objective of treatment is to prevent or control the complications associated with DVT and PAA.…”
Section: Introductionmentioning
confidence: 99%